Analysis of Translation Technique Used in Translating a Poetry titled “Alone” by Edgar Allan Poe on Channel YouTube “MDV Translation” - Efriyani, Mira; Inayah, Ratih; Syaputri, Wuri; Widyasari, Widyasari (Universitas Andalas, 2025)
This study aims to identify the translation techniques used in translating Edgar Allan Poe's poem